Teachers’ Instruction Simulation through Hots in English Writing - Ainul Asmah; Syamsu Tang; Lababa; Sam Hermansyah (MultiTech Publisher, 2024)
This research aims to explore how teachers simulate instruction through Higher Order Thinking Skills (HOTS) in English writing, with a focus on English teachers at SMP Negeri 3 Panca Rijang. Using a qualitative research method, the study investigates the strategies teachers use to stimulate students through HOTS in English classes and evaluates the impact and effectiveness of these strategies on students' writing abilities. The findings reveal that teachers encourage students to regularly use English in daily activities and expand their vocabulary through reading. These strategies effectively foster critical thinking, enabling students to analyze problems and approach English writing more systematically. The implementation of HOTS in teaching has a significant positive impact on students' learning outcomes, particularly in enhancing their analytical and creative thinking skills. The research concludes that the use of HOTS greatly improves the English learning process, contributing to the development of students' cognitive and problem-solving skills.